Relationships Between Psychological, Sleep, and Physical Activity Measures and Somatosensory Function in People With Peripheral Joint Pain: A Systematic Review and Meta‐Analysis. Issue 2 (5th September 2020) - Othman, Rani; Jayakaran, Prasath; Swain, Nicola; Dassanayake, Suranga; Tumilty, Steve; Mani, Ramakrishnan
Abstract: Objective: Alteration in somatosensory function has been linked to pain experience in individuals with joint pain. In this systematic review we aimed to establish the level of evidence of associations between psychological, social, physical activity, and sleep measures and somatosensory function that were assessed via quantitative sensory testing (QST) among individuals with joint pain. Methods: A comprehensive literature search was conducted in 6 electronic databases from their inception to July 2019. Two reviewers independently assessed the methodological quality using a modified Quality in Prognostic Studies (QUIPS) tool and supplemented with recommendations from the Critical Appraisal and Data Extraction for Systematic Review of Prediction Modelling Studies (CHARMS) checklist and the Quality Assessment of Diagnostic Accuracy Studies (QUADAS‐2) tool. The level of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) system. Data were pooled to evaluate the strength of the relationships of interest. Results: Seventeen studies related to joint pain were included. Pain catastrophizing, depression, anxiety, and physical activity level have been shown to have a significant (small to fair) association with several QST measures. Pressure pain threshold (PPT) is the only measure that was found to be consistently correlated with all the domains. The overall quality of evidence for all factors ranged from very low to moderate. Subgroup analysis revealed a stronger association for depression and pain catastrophizing and PPT and temporal pain summation in individuals with shoulder pain. Conclusion: Psychological factors and physical activity levels are associated with somatosensory function in people with joint pain. These factors need to be adjusted when establishing predictive relationships between somatosensory function and pain outcomes in individuals with joint pain.